2012
DOI: 10.1038/modpathol.2011.200
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and classical Hodgkin lymphoma: a description of 10 cases

Abstract: B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and classical Hodgkin lymphoma, is a diagnostic provisional category in the World Health Organization (WHO) 2008 classification of lymphomas. This category was designed as a measure to accommodate borderline cases that cannot be reliably classified into a single distinct disease entity after all available morphological, immunophenotypical and molecular studies have been performed. Typically, these cases share feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…The two most common subtypes of DLBCL are germinal center B-cell (GCB) origin and activated B-cell (ABC) phenotype, with the ABC subtype recognized as having a more aggressive clinical course than the GCB subtype (64,65). Alternative subtypes include composite lymphoma (when two or more distinctly different types of lymphoma occur in the same tissue or organ simultaneously) (66) and unclassified lymphomas, which cannot be clustered with other morphological subtypes (67). This cohort included 31 ABC, 52 GCB, 10 unclassified, and 8 samples categorized as "other or composite" (27).…”
Section: Methodsmentioning
confidence: 99%
“…The two most common subtypes of DLBCL are germinal center B-cell (GCB) origin and activated B-cell (ABC) phenotype, with the ABC subtype recognized as having a more aggressive clinical course than the GCB subtype (64,65). Alternative subtypes include composite lymphoma (when two or more distinctly different types of lymphoma occur in the same tissue or organ simultaneously) (66) and unclassified lymphomas, which cannot be clustered with other morphological subtypes (67). This cohort included 31 ABC, 52 GCB, 10 unclassified, and 8 samples categorized as "other or composite" (27).…”
Section: Methodsmentioning
confidence: 99%
“…During the first meeting in the LYSA-P, the panel of 12 hematopathologists (ATG, TM, DD, PD, BF, CL, MP, LM, DC, BB, PG, CC) established a consensus for inclusion criteria based on previous pathological descriptions of MGZL from the literature. [2][3][4][5]9 They identified 4 situations or subgroups, which are presented in the results section, and in Table 1 and Figure 1, to analyze patients' characteristics and outcomes. As a second step, the panel reviewed all the cases with a multi-head microscope during 3 meetings.…”
Section: Pathological Definition Of Mgzl and Inclusion Criteriamentioning
confidence: 99%
“…[2][3][4][5] Although more recent publications defined a particular methylation profile for this entity, 6,7 and a particular immunohistochemistry scoring system to distinguish it from CHL and PMBCL, 8 there is a need for clarification of the clinico-pathological diagnostic criteria for MGZL. Previous retrospective studies 4,5,[9][10][11][12] (including from 2 to 112 cases) showed that patients with an MGZL had a poorer outcome than patients with a PMBCL or diffuse large B-cell lymphoma (DLBCL). The poor prognosis was confirmed by the prospective study of the National Cancer Institute that included 24 MGZL cases treated with rituximab and an intensified chemotherapy regimen (namely DA-EPOCH-R: dose adapted etoposide, prednisolone, oncovin, cyclophosphamide, doxorubicin) with a shorter progression-free survival (PFS) and overall survival (OS) as compared with PMBCL.…”
Section: Introductionmentioning
confidence: 99%
“…Some cases can show CD23 expression (present in PMBCL and usually absent in cHL). 23 The prognosis seems to be poorer than either cHL or PMBCL and some authors favour the concept of "gray zone lymphomas" to be diffuse large B-cell lymphomas with aberrant immunophenotypes and therefore to benefit from therapies for aggressive large B-cell lymphomas.…”
Section: Primary Cutaneous Dlbcl Leg Type (Pcdlbcl-lt)mentioning
confidence: 98%